Tópicos da história da Matemática como exemplificadores e motivadores para a aprendizagem matemática nas escolas de Lago do Junco (MA) - CARMO, Antonio Hideraldo Medeiros do (2017)
This work sought to provide the public interested in the subject, the elements that allow them to reflect and to decide, in a clear and safe way, about the application of the History of the Mathematics as teaching methodology for the qualitative improvement of mathematical learning. As well as its use to exemplify its applicability as a science and to stimulate the motivation in the teaching and learning process. The connection between Mathematics and its history allowed the elaboration, organization, monitoring and analysis of results through the application of activities and seminars. The guiding question was to answer: “What are the benefits of the History of Mathematics in the math lessons for learning?”. In this qualitative research, the action research what was carried out at the Jos´e Malaquias High School, with students enrolled in the third grade of the morning period. The analysis of the information obtained allowed to verify that the use of historical mathematical episodes, presented and described as indicated in this work, presented new possibilities of motivation, of exemplification of the importance of this science and real situations that aim at the interaction and the socialization of knowledge among the students. The results indicated a motivational link between the teaching of mathematics and its history, facilitating the understanding of the importance of this science to current society, which contributed to the understanding of new contents and the improvement in the quality of learning.